The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1039/c4cp00906a
|View full text |Cite
|
Sign up to set email alerts
|

Improved H2S gas sensing properties of ZnO nanorods decorated by a several nm ZnS thin layer

Abstract: To avoid a spontaneous reaction between ZnO gas sensing materials and detected H2S gas, ZnO nanorods decorated with a several nm ZnS thin layer were designed. The ZnS-decorated layer was prepared by passivating oriented ZnO nanorods in a H2S atmosphere. The effect of the passivation processes on the H2S sensing properties was investigated. It was found that ZnO nanorods decorated with a 2 nm-thick ZnS layer possessed a repeatable and superior response to ppm-level H2S at room temperature. Moreover, a confineme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 25 publications
0
33
0
1
Order By: Relevance
“…Qi et al reported the growth of vertically oriented ZnO NRs on flat ceramic substrates for improved H 2 S sensor fabrication [147]. They passivated ZnO NRs with an additional layer of ZnS to enhance sensor response and stability.…”
mentioning
confidence: 99%
“…Qi et al reported the growth of vertically oriented ZnO NRs on flat ceramic substrates for improved H 2 S sensor fabrication [147]. They passivated ZnO NRs with an additional layer of ZnS to enhance sensor response and stability.…”
mentioning
confidence: 99%
“…Initial findings suggested that the sensing element was highly selective towards hydrogen sulfide when compared to ammonia, acetone, toluene, ethanol, methanol, acetaldehyde, dimethylsulfide. The high selectivity towards hydrogen sulfide might be due to the spontaneous exothermic reaction between ZnO surface and hydrogen sulfide [17,18]. Fig.…”
Section: Resultsmentioning
confidence: 98%
“…In other words, there is an irreversible reaction occurring between the ZnO layer and H2S gas when the sensor is exposed to H2S gas at room temperature. Previous studies have revealed that H2S can spontaneously react with ZnO based on the following formula: [23,[27][28][29] ZnO+H2S(ads) → ZnS+H2O…”
Section: Gas Sensing Performance and The Sensing Mechanismmentioning
confidence: 99%
“…Therefore, ZnO component in the nanocomposite layer can act as the active capturing and adsorption sites for the H2S gas. In addition, the adsorbed H2S molecules can spontaneously react with the ZnO nanoparticles to form ZnS [26][27][28][29], which has a lower density and higher mole weight than those of the ZnO. Therefore, the formation of ZnS will result in decreases of pore sizes and total pore volumes in the layer, which lead to an increase of layer elastic modulus, thus resulting in a significant increase of sensor's response.…”
Section: Introductionmentioning
confidence: 99%